Efektivitas Penyediaan Washtafel yang Ergonomis Terhadap Peningkatan Keterampilan Menyikat Gigi Anak-Anak TK Dharma Wiweka Denpasar Tahun 2025 - Anak Agung Gede Agung; Ni Ketut Ratmini; I Nyoman Wirata; Ni Ketut Nuratni (Jurnal Kesehatan Gigi (Dental Health Journal), 2026)
The prevalence of dental and oral health remains a problem in every province in Indonesia, including Bali. Preschool-aged children are one group vulnerable to dental and oral diseases because they generally still have behaviors that do not support dental health. Teeth in kindergarten children are generally still primary teeth (primary teeth), with tooth structure and morphology that are susceptible to caries. Data from the 2018 Bali provincial health risk (Riskesda) explained that the incidence of dental caries by age group 3-4 years was 41.8%. In Denpasar City, the 3-4 year age group suffered from dental caries as much as 14.8%. As age increases, the prevalence of dental caries also increases. The still low behavior of brushing teeth properly is one of the causes. Low tooth brushing behavior is likely due to a lack of knowledge, facilities and infrastructure for brushing teeth, such as ergonomic sinks. The purpose of this study was to determine the effect of ergonomic sinks on changes in students' tooth brushing behavior. The research method used pre- and post-observation of tooth-brushing behavior, namely behavior before and after education and practice of brushing teeth using ergonomic sinks in kindergarten. The results showed that after education and daily brushing habits using ergonomic sinks, most students' behavior changed to the adequate, good, and very good categories. This indicates a positive change in tooth-brushing behavior, from the majority of students initially categorized as needing guidance to the majority being categorized as good. The statistical test results showed a significant effect on student behavior change. The conclusion of this study is that education through the provision of ergonomic sinks has a significant effect on students' tooth-brushing behavior. It is recommended that kindergarten caregivers continue to provide education and remind children to brush their teeth at least twice a day.